Konsep dan Implementasi TPACK pada Pembelajaran di Sekolah Menengah Pertama - Akbar, Hilda Marwani; Event, Diana; Heviana, Elsi; Rahayu, Ivo Gana; Darmansyah, Darmansyah; Demina, Demina (Komunitas Manajemen Kompetitif, 2024)
Important for teachers to adopt information technology in the learning process in the 21st Century. Teachers are also required to have adequate pedagogical competence where in carrying out learning it is hoped that it is not teacher centered but student centered and technology based. One of the learning frameworks developed by focusing on technology, pedagogy and teaching materials is TPACK. This research aims to describe the concept and implementation of TPACK in learning in junior high schools. The research method is descriptive qualitative research with a literature study method. The findings show that there are seven components in the TPACK concept, namely technological knowledge, pedagogical knowledge, content knowledge, technological pedagogical knowledge, technological content knowledge, pedagogical content knowledge, and technological pedagogical content knowledge. The form of implementation of TPACK in junior high schools is carried out in various ways that utilize technology in the learning process, such as the use of animated videos in learning. The implementation of TPACK has had high success in supporting the achievement of learning objectives so it is hoped that teachers can use this model to improve student learning outcomes. Keywords: TPACK Implementation, TPACK Concept, Junior High School